1990
DOI: 10.1111/j.1476-5381.1990.tb14683.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a selective 5‐HT2 agonist, DOI, on 5‐HT neuronal firing in the dorsal raphe nucleus and 5‐HT release and metabolism in the frontal cortex

Abstract: Systemic administration of the 5‐HT2 agonist 1‐(2,5‐dimethoxy‐4‐iodophenyl)‐2‐aminopropane (DOI) (50 and 100 μg kg−1, i.v.) inhibited dorsal raphe neuronal firing. DOI (100 μg kg−1, i.v.) also produced a decrease in extracellular 5‐hydroxytryptamine (5‐HT) and 5‐hydroxyindoleacetic acid (5‐HIAA) in the frontal cortex measured by microdialysis. However, local administration of DOI into the frontal cortex produced no change in extracellular 5‐HT and 5‐HIAA at any dose given (1, 10 and 100 ng). The results demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(23 citation statements)
references
References 9 publications
0
23
0
Order By: Relevance
“…In addition, Carli and Samanin (1992) have found that 5-HT 2 receptor agonists (lysergic acid diethylamide and quipazine) cause a ritanserin-sensitive deterioration in choice accuracy and omission in the five-choice serial reaction time task, as seen here with the highest dose of DOI. In contrast, there is evidence suggesting presynaptic inhibition of serotonergic activity by DOI (Wright et al 1990). Altogether, DOI may not only activate 5-HT 2A receptors postsynaptically but also produce an indirect serotonergic inhibition (i.e.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In addition, Carli and Samanin (1992) have found that 5-HT 2 receptor agonists (lysergic acid diethylamide and quipazine) cause a ritanserin-sensitive deterioration in choice accuracy and omission in the five-choice serial reaction time task, as seen here with the highest dose of DOI. In contrast, there is evidence suggesting presynaptic inhibition of serotonergic activity by DOI (Wright et al 1990). Altogether, DOI may not only activate 5-HT 2A receptors postsynaptically but also produce an indirect serotonergic inhibition (i.e.…”
Section: Discussionmentioning
confidence: 83%
“…If 8-OH-DPAT preferentially acts on the dorsal raphé, the stimulation of 5-HT 1A somatodendritic autoreceptors would reduce serotonergic neuronal firing and 5-HT release (Sprouse and Aghajanian 1988;Wright et al 1990). In contrast, the activation of postsynaptic 5-HT 1A receptors increases wakefulness and leads to its antidepressant-like activity (Leonard 1996;Bjorvatn and Ursin 1998).…”
Section: Discussionmentioning
confidence: 98%
“…Parallel effects on DRN discharge and 5-HT terminal release has also been shown for other compounds such as the 5-HT 1A agonist 8-OH-DPAT, which decreases both DRN discharge and terminal 5-HT release (Crespi et al 1990), 5-HT 2 agonists (Wright et al 1990), and serotonin-selective reuptake inhibitors (Romero et al 1996). Furthermore, parallel effects of CRF on LC discharge and terminal norepinephrine release have been demonstrated (Page and Abercrombie 1999;Curtis et al 1997;Smagin et al 1995).…”
Section: Discussionmentioning
confidence: 90%
“…Either lateral attack, that would be part of an offensive strategy similar to the territorial behavior of a dominant male against an intruder, or frontal attack, that would be part of a defensive strategy similar to the reaction of a cornered animal to an inescapable threat (Lucion and De Almeida 1996), decreased after the administration of 8-OH-DPAT. Since 8-OH-DPAT decreases firing rate of raphe nuclei (Wright et al 1990;Jacobs and Fornal 1991), we may conclude that a reduction in the activity of the median raphe nucleus decreases maternal aggression.…”
Section: Discussionmentioning
confidence: 97%